The Influence Of Understanding The Code Of Ethics Of The Accountant Profession And Student Intelligence On The Ethical Behavior Of Accounting Students - Agus Sumanto; Mega Rosdiana; Rica Wuryaningrum (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
According to Nur Anwar (Nur Anwar: 2019) various problems related to ethical behavior have often occurred, one example of which is financial irregularities found in the country. The behavior of these deviations does not only occur in the scope of workers, but also appears in college. In this case, the role of students in achieving economic progress in a country is no less important than other components such as the country's economic relations, the amount of money in circulation or circulating in society. Students have an important role in upholding the name of their country in doing what is considered the best, especially students from accounting study programs in disclosing the accountability of financial reporting. However, currently there is unethical behavior that has occurred in universities such as copying or cheating, friends' answers being copied, asking for attendance signatures and cheating. Many students compete with each other to achieve academic achievement in order to get high or good grades in ways that are considered unethical such as copying or looking at friends' answers during exams or quizzes, and other unethical methods. If this is allowed to continue, it is feared that in the long term there will be graduates from accounting study programs who do not have good integrity